Light Emission from Rare-Earth Doped Silicon Nanostructures. (13th April 2008) - Li, J.; Zalloum, O. H. Y.; Roschuk, T.; Heng, C. L.; Wojcik, J.; Mascher, P.
Abstract : Rare earth (Tb or Ce)-doped silicon oxides were deposited by electron cyclotron resonance plasma-enhanced chemical vapour deposition (ECR-PECVD). Silicon nanocrystals (Si-ncs) were formed in the silicon-rich films during certain annealing processes. Photoluminescence (PL) properties of the films were found to be highly dependent on the deposition parameters and annealing conditions. We propose that the presence of a novel sensitizer in the Tb-doped oxygen-rich films is responsible for the indirect excitation of the Tb emission, while in the Tb-doped silicon-rich films the Tb emission is excited by the Si-ncs through an exciton-mediated energy transfer. In the Ce-doped oxygen-rich films, an abrupt increase of the Ce emission intensity was observed after annealing at1200 ∘ C. This effect is tentatively attributed to the formation of Ce silicate. In the Ce-doped silicon-rich films, the Ce emission was absent at annealing temperatures lower than1100 ∘ C due to the strong absorption of Si-ncs. Optimal film compositions and annealing conditions for maximizing the PL intensities of the rare earths in the films have been determined. The light emissions from these films were very bright and can be easily observed even under room lighting conditions.